Aquatic biomonitoring of Giardia cysts and Cryptosporidium oocysts in peninsular Malaysia - Lee, S.C.; Ngui, R.; Tan, T.K.; Roslan, M.A.; Ithoi, I.; Lim, Y.A.L. (Springer Verlag (Germany), 2014)
An aquatic biomonitoring of Giardia cysts and Cryptosporidium oocysts in river water corresponding to five villages situated in three states in peninsular Malaysia was determined. There were 51.3 % (20/39) and 23.1 % (9/39) samples positive for Giardia and Cryptosporidium (oo)cysts, respectively. Overall mean concentration between villages for Giardia cysts ranged from 0.10 to 25.80 cysts/l whilst Cryptosporidium oocysts ranged from 0.10 to 0.90 oocysts/l. Detailed results of the river samples from five villages indicated that Kuala Pangsun 100 % (9/9), Kemensah 77.8 % (7/9), Pos Piah 33.3 % (3/9) and Paya Lebar 33.3 % (1/3) were contaminated with Giardia cysts whilst Cryptosporidium (oo)cysts were only detected in Kemensah (100 %; 9/9) and Kuala Pangsun (66.6 %; 6/9). However, the water samples from Bentong were all negative for these waterborne parasites. Samples were collected from lower point, midpoint and upper point. Midpoint refers to the section of the river where the studied communities are highly populated. Meanwhile, the position of the lower point is at least 2 km southward of the midpoint and upper point is at least 2 km northward of the midpoint. The highest mean concentration for (oo)cysts was found at the lower points [3.15 ± 6.09 (oo)cysts/l], followed by midpoints [0.66 ± 1.10 (oo)cysts/l] and upper points [0.66 ± 0.92 (oo)cysts/l]. The mean concentration of Giardia cysts was highest at Kuala Pangsun (i.e. 5.97 ± 7.0 cysts/l), followed by Kemensah (0.83 ± 0.81 cysts/l), Pos Piah (0.20 ± 0.35 cysts/l) and Paya Lebar (0.10 ± 0.19 cysts/l). On the other hand, the mean concentration of Cryptosporidium oocysts was higher at Kemensah (0.31 ± 0.19 cysts/l) compared to Kuala Pangsun (0.03 ± 0.03cysts/l). All the physical and chemical parameters did not show significant correlation with both protozoa. In future, viability status and molecular characterisation of Giardia and Cryptosporidium should be applied to identify species and genotypes/subgenotypes for better understanding of the epidemiology of these waterborne parasites.